Precipitous Resolution of Type-A Intramural Hematoma with Medical Management in a Patient with Metastatic Stage 4 Renal Cell Carcinoma - Velasquez, Camilo A.; Bin Mahmood, Syed Usman; Zafar, Mohammad A.; Brownstein, Adam J.; Saeyeldin, Ayman; Ziganshin, Bulat A.; Elefteriades, John A. (International Journal of Angiology, 2017)
Intramural hematoma (IMH) is a variant form of aortic dissection characterized by involvement of the aortic media without the presence of an overt intimal flap. Surgical extirpation is the standard of care for type-A IMH in the Western world. However, a conservative approach with anti-impulse therapy has been advocated especially in Japan as a viable alternative. Here, we report a case of an elderly male patient with a history of metastatic stage 4 renal cell carcinoma who was treated with anti-impulse therapy for an acute type-A IMH. Blood pressure stabilization and continuous monitoring resulted in complete resolution of the IMH within 6 days. This report illustrates how immediate medical management in patients with acute type-A IMH who are not surgical candidates can alleviate the progression or even lead to regression as early as 1 week after initiating anti-impulse therapy.
Keywords: dissection; dissecting aneurysm; hematoma; intramural hematoma; medical therapy; resolution; type-A dissection